FORMATION OF PERFORMANCE SKILLS IN STUDENTS THROUGH INDEPENDENT LEARNING - Bobokulova Moxinur Jamshid qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the pedagogical and methodological significance of independent learning in developing students’ performance skills. The study explores effective strategies for enhancing technical and artistic abilities through independent study, including the use of electronic resources, interactive methods, and project-based learning. The article also discusses how independent learning fosters selfassessment, reflective practice, and creative development in music students.